The Prospect Of Diesohol In Facing Fossil Fuel Crissis - M.C. Tri Atmodjo (Bandar Lampung University (UBL), 2013)
The crisis of fosil (Petroleum) fuel around Lampung municipal and other districs in Indonesia need some alternative solution with SWOT analysis. The Diesohol can be applied both in gasoline engine and diesel engine respectively. The Diesohol which the mixing 2 percent of bioethanol and 98 percent of biodiesel or diesel oil was able to use in diesel engine properly. Although only 2 percent of bioethanol applied in diesohol but this opportunity will decrease fosil fuel consumption in the future. The Strength of Diesohol is The raw material is renewable which obtain from biomass around us, The Weakness is difficult to mix between bioethanol and biodiesel without agitator or stirrer. The Opportunity is circumstances kindly and under govenment national program. The threats is CO2 gas which by product in bioethanol production and the higher cost production of diesohol.rather than fossil fuel.